Strategi Pendidikan Konseling Islam untuk Meningkatkan Religiusitas di Pondok Pesantren Al-Hadi Yogyakarta - Ach. Sofauzzad; Eka Varida Kusuma (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Education plays a crucial role in shaping the personality, morals, and spiritual values of students. In the Islamic perspective, education is not solely focused on the mastery of knowledge but also includes the cultivation of noble character, the strengthening of faith, and the enhancement of religiosity as a form of devotion to Allah Swt. Islamic boarding schools (pondok pesantren), as traditional Islamic educational institutions, have a strategic role in instilling these values through religious activities, the teaching of classical Islamic texts (kitab kuning), and the habituation of virtuous behavior. Pesantren serve not only as centers of learning but also as institutions for character formation and spiritual development. However, the forces of globalization and modernization bring new challenges in the form of cultural, technological, and informational influences that often conflict with Islamic values. Therefore, pesantren are required to develop adaptive, innovative, and relevant educational strategies that align with contemporary needs without losing their Islamic identity. One effective approach is the implementation of Islamic counseling, a process of psychological and spiritual guidance grounded in the Qur’an and Sunnah. Through this counseling, students are expected to strengthen their faith, enhance their religiosity, and develop moral resilience in facing the dynamics of modern life based on strong Islamic values.